2023
DOI: 10.1002/mp.16593
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation and new recommendations in the use of Gafchromic EBT3 film

Abstract: BackgroundGafchromic film's unique properties of tissue‐equivalence, dose‐rate independence, and high spatial resolution make it an attractive choice for many dosimetric applications. However, complicated calibration processes and film handling limits its routine use.PurposeWe evaluated the performance of Gafchromic EBT3 film after irradiation under a variety of measurement conditions to identify aspects of film handling and analysis for simplified but robust film dosimetry.MethodsThe short‐ (from 5 min to 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…44 Although some have suggested that the dynamic range of Gafchromic EBT3 film is limited to doses less than 10 Gy, particularly for the red channel, 14,25 several others have either used or reported the feasible use of Gafchromic EBT3 film at higher dose ranges using multi-channel dosimetric analysis of film by incorporating the green and blue channels. 9,[25][26][27][31][32][33] In this study and in a prior study, 31 we have demonstrated the feasible and accurate use of Gafchromic EBT3 film at doses ≥ 40 Gy using a single polynomial equation for netOD values measured in the red channel allowing for ease of use in single-channel film dosimetry for high-dose settings. Similar to previous recommendations for Gafchromic EBT3 film, AAPM's TG-191 report states the recommendation that the use of OSLDs and TLDs be limited to a cumulative dose of 10 Gy because of reported changes in sensitivity and supralinear behavior caused by the population of charge carriers in the deep traps.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…44 Although some have suggested that the dynamic range of Gafchromic EBT3 film is limited to doses less than 10 Gy, particularly for the red channel, 14,25 several others have either used or reported the feasible use of Gafchromic EBT3 film at higher dose ranges using multi-channel dosimetric analysis of film by incorporating the green and blue channels. 9,[25][26][27][31][32][33] In this study and in a prior study, 31 we have demonstrated the feasible and accurate use of Gafchromic EBT3 film at doses ≥ 40 Gy using a single polynomial equation for netOD values measured in the red channel allowing for ease of use in single-channel film dosimetry for high-dose settings. Similar to previous recommendations for Gafchromic EBT3 film, AAPM's TG-191 report states the recommendation that the use of OSLDs and TLDs be limited to a cumulative dose of 10 Gy because of reported changes in sensitivity and supralinear behavior caused by the population of charge carriers in the deep traps.…”
Section: Discussionmentioning
confidence: 60%
“…1,2,6,7,[9][10][11]32,33 The films were scanned at 24 h post-irradiation using an Epson 10000XL flatbed scanner (Seiko Epson Corporation, Nagano, Japan) and analyzed using ImageJ and MATLAB using the red channel only as previously described. 31 2.1.2 Thermoluminescent dosimeters (TLDs) LiF:Mg,Ti TLD powder (∼25 mg) was packaged in single-use plastic envelopes (1 cm × 1 cm) before their irradiation. At 24 h after irradiation, the weight of the powdered TLD was measured by using a precision lab scale by subtracting the weight of the plastic envelope from the total weight of the TLD packet.…”
Section: Gafchromic Ebt3 Filmmentioning
confidence: 99%
See 1 more Smart Citation